2000
DOI: 10.1002/(sici)1097-0215(20000415)86:2<276::aid-ijc19>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant vitamins reduce normal tissue toxicity induced by radio-immunotherapy

Abstract: Our purpose was to determine whether the administration of anti‐oxidant vitamins could reduce dose‐limiting toxicity from radio‐immunotherapy (RAIT) and thereby allow higher escalation of RAIT doses. Lipophilic vitamins A and E were administered i.p. and hydrophilic vitamin C was administered i.m. for 14 days (3 days pre‐RAIT through 11 days post‐RAIT) alone or with bone marrow transplantation (BMT) to either BALB/c mice for toxicity studies or to nude mice bearing s.c. GW‐39 human colonic cancer xenografts fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Lipid peroxidation products increased with chemotherapy have been reported to decrease free radical scavengers antioxidant vitamins, such as vitamins A, E, and C 4,26 . In another in vivo and in vitro study, the use of vitamins E, A, and C against oxidative stress caused by chemotherapy has been found to enhance the therapeutic effect and also protect normal cells against apoptosis 5 . It has been reported in a cell culture and animal model that the combinations of vitamins A, B6, B12, C, D, and E with β-caroten protected against adverse effects of chemotherapy prolonged survival time and increased response to treatment 26 .…”
Section: Discussionmentioning
confidence: 97%
“…Lipid peroxidation products increased with chemotherapy have been reported to decrease free radical scavengers antioxidant vitamins, such as vitamins A, E, and C 4,26 . In another in vivo and in vitro study, the use of vitamins E, A, and C against oxidative stress caused by chemotherapy has been found to enhance the therapeutic effect and also protect normal cells against apoptosis 5 . It has been reported in a cell culture and animal model that the combinations of vitamins A, B6, B12, C, D, and E with β-caroten protected against adverse effects of chemotherapy prolonged survival time and increased response to treatment 26 .…”
Section: Discussionmentioning
confidence: 97%
“…This finding is supported by the studies of Blumenthal et al , who found that a dietary supplement of vitamins A, C and E (administered in diet at 10× the daily requirement) increased the maximum tolerated dose of 131 I-labeled radiolabeled antibody administered to mice ( 131 I-MN-14) (10). Other studies have shown that antioxidant diet supplementation can be an effective treatment to reduce radiation death in rodents (47, 48).…”
Section: Discussionmentioning
confidence: 56%
“…Vitamin C and E supplements reduced bleeding and diarrhea in patients with chronic radiation proctitis due to previous pelvic irradiation (27). A combination of vitamins A, C and E reduced bone marrow toxicity caused by radioimmunotherapy with 131 I-labeled antibodies (10). Furthermore, we have demonstrated a diet enriched in vitamins A, C and E (vitamin ACE) protects intestinal transport of these nutrients under acute irradiation conditions (4).…”
Section: Introductionmentioning
confidence: 99%
“…Mixtures of radioprotectors offer a means to both improve DMF values and increase coverage with respect to the types of radiation damage that can be protected against. A combination of vitamins A, C and E reduced bone marrow toxicity caused by radioimmunotherapy with 131 I labeled antibodies (Blumenthal et al 2000) and prevented reductions in intestinal nutrient transport caused by whole-body acute and chronic irradiation (Roche et al 2011, Roche et al 2015). …”
Section: Introductionmentioning
confidence: 99%